Effect of Frozen Storage on the Water- Holding Capacity and pH of Broiler Chicken cut-up Parts (Gallus gallus domesticus) - Ghimire, Arjun; Parajuli, Pawan (Himalayan Journal of Science and Technology, 2020)
Broiler chickens (Gallus gallus domesticus) were collected from local chicken suppliers of Dharan (26.8065° N, 87.2846° E), Nepal, and slaughtered to prepare the cut-up parts (breast, drumstick, dorso, wings, and thigh). They were vacuum packed in polythene bags and frozen stored (-21.5 ±3.5ºC) for 45 days to study the effect of frozen storage on the water holding capacity (WHC) of meat. Cooking loss, drip loss, and pH changes were analyzed at 5 days intervals during storage and the data were analyzed using Genstat® v 12.1.The cut-up parts showed a significant change (p<0.05) in pH, cooking loss, and drip loss during 45 days of frozen storage. The pH decreased while the drip loss and the cooking loss increased gradually upon storage. The pH was found to be varied among the cut-up parts with a minimum pH scale of 5.25 for wings, followed by 5.3 for thigh, at the end. The highest drip loss of 6.11% was observed in wings after 5 days of storage which ended up to 8.97% after 45 days of frozen storage while drumstick and thigh samples showed significantly lower drip loss of 6.02%, and 5.43% respectively. The change in cooking loss showed a similar pattern as that of drip loss with a significantly higher value of 37.36% in the breast while it showed no significant difference in drumstick, dorso, and thigh meat. Thus, the study reveals that freezing of broiler chicken meats for a prolonged period adversely affects the WHC of meat